Wojewódzka komisja ds. orzekania o zdarzeniach medycznych a wojewoda — role i zakresy odpowiedzialności w zakresie przetwarzania danych osobowych - Bielak-Jomaa, Edyta (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The article discusses the problem of the relationship between the commission for the adjudication of the medical event and the provincial governor in terms of establishment medical event with regard to data processing. The issue is important from the point of view of determining the tasks, roles and responsibilities of these entities for the processing of personal data. It is important from a practical point of view to indicate whether there is a relationship between these authorities of separate administrators or co-administration of personal data.
Keywords: voivodship commission for adjudication of a medical event; voivode; personal data; medical data; personal data processing; joint controller